Liquidity at Risk : Joint Stress Testing of Solvency and Liquidity - Cont, Rama (IMF Working Papers; Working Paper ;, 2020)
The traditional approach to the stress testing of financial institutions focuses on capital adequacy and solvency. Liquidity stress tests have been applied in parallel to and independently from solvency stress tests, based on scenarios which may not be consistent with those used in solvency stress tests. We propose a structural framework for the joint stress testing of solvency and liquidity: our approach exploits the mechanisms underlying the solvency-liquidity nexus to derive relations between solvency shocks and liquidity shocks. These relations are then used to model liquidity and solvency risk in a coherent framework, involving external shocks to solvency and endogenous liquidity shocks arising from these solvency shocks. We define the concept of 'Liquidity at Risk', which quantifies the liquidity resources required for a financial institution facing a stress scenario. Finally, we show that the interaction of liquidity and solvency may lead to the amplification of equity losses due to funding costs which arise from liquidity needs. The approach described in this study provides in particular a clear methodology for quantifying the impact of economic shocks resulting from the ongoing COVID-19 crisis on the solvency and liquidity of financial institutions and may serve as a useful tool for calibrating policy responses.